Pirfenidone Induced Photosensitivity Reaction in a Patient with Idiopathic Pulmonary Fibrosis - Usharani, Pingali; Ramakanth, GSH; Paramjyothi, GK; Vijayalakshmi, S; Reddy, D Bhargav (Indian Journal of Case Reports, 2016)
Drug-induced photosensitivity refers to the development of cutaneous disease as a result of combined effects of a chemical and light. Photosensitivity reactions may result from systemic medications and topically applied compounds. Pirfenidone is known to cause photosensitivity reactions, rash, pruritus and dry skin at high doses. However, similar adverse reactions with low doses of Pirfenidone have not been reported. We report a case of photosensitivity reaction induced by low- dose Pirfenidone in a patient with idiopathic pulmonary fibrosis (IPF).